Politipraktikere og deres syn på politiutdanningen - Geir Aas (Nordisk Politiforskning)
Summary The police as a social institution and the use of police force are often on the agenda of public debate. Thus, police training is regularly in the media spotlight, too. This article presents fresh research on what police practitioners think about the Norwegian police university college as a basis for police practice. The police university college is, in accordance with guidelines from NOKUT (Norwegian Agency for Quality Assurance in Education), required to ensure the quality of its education. By two tests, the police university college has obtained knowledge about how graduated police officers and their superiors consider police training. These surveys are conducted by using questionnaires (questback) in the internal police net. This study presents qualitative data on police officers’ views on police training that will enable them to perform operational policing. The police leaders who emphasize general knowledge and skills for police work, give both education and the graduates good references. When it comes to specific skills for using force in time-critical situations, the graduates are placed in a critical light.